# 9n-(7n+10)=6-(2n-5)

## Simple and best practice solution for 9n-(7n+10)=6-(2n-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 9n-(7n+10)=6-(2n-5) equation:

9n-(7n+10)=6-(2n-5)
We move all terms to the left:
9n-(7n+10)-(6-(2n-5))=0
We get rid of parentheses
9n-7n-(6-(2n-5))-10=0

We calculate terms in parentheses: -(6-(2n-5)), so:
6-(2n-5)
determiningTheFunctionDomain
-(2n-5)+6
We get rid of parentheses
-2n+5+6
We add all the numbers together, and all the variables
-2n+11
Back to the equation:
-(-2n+11)

We add all the numbers together, and all the variables
2n-(-2n+11)-10=0
We get rid of parentheses
2n+2n-11-10=0
We add all the numbers together, and all the variables
4n-21=0
We move all terms containing n to the left, all other terms to the right
4n=21
n=21/4
n=5+1/4

`